Responses, Interest in Learning, and Ability to Understand Two Dimensional Figure Concepts for Junior High School Students: A Study of the Use of the Quizizz Application - Mohammad Syaifuddin; Elfrida Rahmasari (Mosharafa: Jurnal Pendidikan Matematika, 2023)
Quizizz sebagai aplikasi evaluasi memiliki peranan penting untuk meningkatkan minat belajar dan pemahaman konsep matematika siswa. Di Indonesia, sudah terdapat beberapa guru menggunakan aplikasi tersebut, namun penggunaan secara luas masih belum optimal. Tujuan penelitian ini mendeskripsikan respons, minat belajar, dan kemampuan pemahaman konsep bangun datar siswa SMP berbantuan aplikasi Quizizz. Penelitian ini berjenis deskriptif kuantitatif. Subjek penelitian adalah 30 siswa SMP. Data diperoleh dari angket dan tes. Analisis data menggunakan teknik deskriptif kuantitatif dengan menghitung total skor respons, minat belajar, dan pemahaman konsep siswa yang dikonversi pada skala 100 dan dikategorilan sangat baik, baik, cukup, dan kurang baik. Hasil penelitian menunjukkan respons dan minat belajar siswa pada pembelajaran bangun datar menggunakan Quizizz berkategori baik. Rata-rata kemampuan pemahaman konsep bangun datar siswa sebesar 66 berkategori cukup baik. Dengan demikian, guru diharapkan menggunakan Quizizz dalam pembelajaran dan evaluasinya sehingga dapat meningkatkan minat siswa belajar dan berlatih kemampuan pemahaman konsep matematika.Quizizz as an evaluation application has an important role in increasing students' interest in learning and understanding mathematical concepts. In Indonesia, there are already several teachers using the application, but its use by teachers widely is still not optimal. The purpose of this study was to describe the response, interest in learning, and the ability to understand the concept of flat shapes for junior high school students with the help of the Quizizz application. This research is quantitative descriptive. The research subjects were 30 junior high school students. Data were obtained from questionnaires and tests. Data analysis used a quantitative descriptive technique by calculating the total response score, learning interest, and students' conceptual understanding converted on a scale of 100 and categorized as very good, good, enough, and not good. The results showed that the responses and students' learning interest in learning flat shapes using Quizizz were in good category. The average ability to understand the concept of a flat shape of 66 students is in a fairly good category. The teachers are expected to use Quizizz in their learning and evaluation so that it can increase students' interest in learning and practicing their ability to understand mathematical concepts.